(untitled) (Medical Forum Monthly, 2020)
Objective: The aim of this study was to evaluate the efficacy of intra-articular TA injection in patients of primary TKA. Study Design: Experimental study Place and Duration of Study: This study was conducted at the Department of Orthopedics Surgery, Lahore General Hospital, Lahore, from October 2018 to March 2020. Materials and Methods: A total of 92 patients undergoing primary cemented TKA were enrolled. Since June 2019 and onwards, we adopted topical TA (n=52) while controls were all those cases (n=40) undergoing TKA between October 2018 to May 2019. Standard medial parapatellar approach with tourniquet were done among all the patients. Patients of topical TA group were given intraarticular 1.5 gram TA diluted to 50 ml normal saline. Transfusion rate, highest hemoglobin drop (preoperative to postoperative lowest levels), highest hematocrit drop (preoperative to postoperative lowest levels), duration of hospitalization along with drainage output and thromboembolic complications were recorded. Results: Out of a total of 92 patients, 35 (38.0%) were male and 57 (62.0%) female. No statistically significant difference was noted in terms of characteristic of study participants among both study groups (P>0.05). When compared to topical TA group, significantly higher drop between preoperative and postoperative hemoglobin levels and hematocrit levels were recorded among controls (p<0.05). Transfusion rate was also high among controls (25.0% vs. 5.8%, p=0.0087). Duration of hospitalization was significantly short among topical TA group (p=0.0181). No significant difference in terms of post-operative complications was seen among both study groups (p>0.05). Conclusion: Topical TA in reducing postoperative blood loss for primary TKA was found to be effective. We consider this technique tobe safe and efficient to our patients undergoing TKA.